KOMODIFIKASI IDEALISME FEMINISME DALAM INDUSTRI MUSIK - Frizky Yulianti (IKOM UMY, 2015)
This research use semiotic analysis of Roland Bartehs to explore visual aspect in Run The World video clip from Beyonce Knowles, This research method con help the researcher to explore meaning and ideology behind the song dan the video clip. By using semiotic, we can find that although the spirit of the song to fight women power, the song and video clip still have contradictions when exploitote women body in provocative dance. The interesting point are Beyonce Knowles tried to represent women as mosculin women in the video clip.